Identification of Molecular Correlations Between DHRS4 and Progressive Neurodegeneration in Amyotrophic Lateral Sclerosis By Gene Co-Expression Network Analysis - Li, Shu; Zhu, Yu; Wei, Caihui; Li, Cheng; Chen, Wenzhi; Jiang, Shishi; Yuan, Dongxiang; Xu, Renshi (Frontiers in Immunology, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease, which has not yet been fully elucidated. With this study, we aim to define and verify candidate effective biomarkers of ALS by bioinformatics. Here, we employed differential expression analysis and weighted gene co-expression network analysis (WGCNA) to identify biomarkers of ALS. We isolated lumbar spinal cord from mice and characterized them using western blot and immunofluorescence to investigate the expression of candidate gene. Additionally, a series of bioinformatics such as enrichment analysis, immune infiltration analysis, protein-protein interaction (PPI) network analysis was used to explore potential mechanisms. Our results show that Dhrs4 expression in the spinal cord was upregulated with the progression of SOD1 G93A mice, and the up-regulation of DHRS4 and its synergistic DHRS3, may be primarily associated with the activation of the complement cascade in the immune system (C1QA, C1QB, C1QC, C3, and ITGB2), which may be a novel mechanism that induces spinal neurodegeneration in ALS. We propose that DHRS4 and its synergistic DHRS3 is a promising molecular marker for detecting ALS progression.